A handbook for Rhythmic Relating in autism: supporting social timing in play, learning and therapy - Daniel, Stuart; Laurie, Matthew; Delafield-Butt, Jonathan T. (Frontiers in Psychology, 2024)
We present a handbook to Rhythmic Relating, an approach developed to support play, learning and therapy with young autistic children, unconventional communicators, and autistic people who have additional learning needs. Rhythmic Relating is based on the Movement Sensing perspective, a growing body of research that recognizes that autistic social difficulties stem from more basic sensory and motor differences. These sensorimotor differences directly affect embodied experience and social timing in communication. The Rhythmic Relating approach acknowledges that autistic/non-autistic interactive mismatch goes both ways and offers bidirectional support for social timing and expressive action in play. This handbook is presented in an accessible fashion, allowing the reader to develop at their own pace through three skill-levels and encouraging time out to practice. We begin with the basics of building rapport (seeing, copying, and celebrating interactional behaviors), introduce the basic foundations of sensory stability, and then move on to developing reciprocal play (using mirroring, matching, looping, and ‘Yes…and’ techniques), and further to understanding sensory impetus (using sensory contours, accents and flows) and its potential in support of social timing. Rhythmic Relating is offered in support of each practitioner’s creative practice and personal sense of fun and humor in play. The model is offered as a foundation for interaction and learning, as a base practice in schools, for Occupational Therapists and Physiotherapists, and can also provide a basis for tailoring creative arts therapies when working with autistic clients.